{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

# 0216 - I run √ 60 2 x 2 on grass and then run on sidewalk...

This preview shows page 1. Sign up to view the full content.

Math 31A 2010.02.16 MATH 31A DISCUSSION JED YANG 1. Optimisation 1.1. Exercise 4.6.15. Find the dimensions of the rectangle of maximum area that can be inscribed in a circle of radius r . Solution. Let x and y be the side lengths. By Pythagorean theorem, they satisfy x 2 + y 2 = 4 r 2 . We want to maximize A = xy . Solve for y = 4 r 2 - x 2 . So A = x 4 r 2 - x 2 . We can maximize A 2 = x 2 (4 r 2 - x 2 ) = 4 r 2 x 2 - x 4 . Differentiate to get ( A 2 ) = 8 r 2 x - 4 x 3 . Critical points are 8 r 2 x - 4 x 3 = 0 so x = 0 or x 2 = 2 r 2 , that is, x = r 2. End points x = 0 , 2 r . We get A (0) = A (2 r ) = 0 and A ( r 2) = 2 r 2 . So area is maximized when x = y = r 2, that is, we have a square. square 1.2. Catching a bus. I am at one corner of a rectangular park with sides 60 and 300 metres. The bus stop is at the opposite corner. I can run on the grass at 5 m/s, and I can skateboard on the sidewalk (along the long side) at 13 m/s. I want to get to the bus stop by running across the park and then skateboarding on the sidewalk. Where should I run to in order to get there the fastest? Solution. Let x be the distance that I skip on the long sidewalk. In otherwords,
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: I run √ 60 2 + x 2 on grass, and then run on sidewalk for 300-x . Dividing by the rates, we get the total travel time is y = 300 − x 13 + √ 60 2 + x 2 5 . Di±erentiating, we get y ′ =-1 13 + x 5 √ 60 2 + x 2 . Setting equal to 0, we solve and get x = 25. Note that if there were a sidewalk on the short side too, then it would be faster to skate along the sidewalk for the entire time instead. Moral: Sometimes it is not good to cut corners. s 2. Basic Integration 2.1. Exercise 4.8.58. Let f ′′ ( t ) = t-cos t , f ′ (0) = 2, f (0) =-2. Find f ′ and f . Solution. By integrating, we see f ′ ( t ) = t 2 / 2-sin t + c . Since f ′ (0) = c = 2, we get f ′ ( t ) = t 2 / 2-sin t + 2. Integrating again to get f ( t ) = t 3 / 6 + cos t + 2 t + d . Since f (0) = 1 + d =-2, we get d =-3, yielding f ( t ) = t 3 /y + cos t + 2 t-3. s...
View Full Document

{[ snackBarMessage ]}

### What students are saying

• As a current student on this bumpy collegiate pathway, I stumbled upon Course Hero, where I can find study resources for nearly all my courses, get online help from tutors 24/7, and even share my old projects, papers, and lecture notes with other students.

Kiran Temple University Fox School of Business ‘17, Course Hero Intern

• I cannot even describe how much Course Hero helped me this summer. It’s truly become something I can always rely on and help me. In the end, I was not only able to survive summer classes, but I was able to thrive thanks to Course Hero.

Dana University of Pennsylvania ‘17, Course Hero Intern

• The ability to access any university’s resources through Course Hero proved invaluable in my case. I was behind on Tulane coursework and actually used UCLA’s materials to help me move forward and get everything together on time.

Jill Tulane University ‘16, Course Hero Intern